NK Cells Equipped With a Chimeric Antigen Receptor That Overcomes Inhibition by HLA Class I for Adoptive Transfer of CAR-NK Cells - Zhuang, Xiaoxuan; Long, Eric O. (Frontiers in Immunology, 2022)
Dominant inhibitory receptors for HLA class I (HLA-I) endow NK cells with high intrinsic responsiveness, a process termed licensing or education, but hinder their ability to kill HLA-I+ tumor cells. Cancer immunotherapy with adoptive transfer of NK cells must overcome inhibitory signals by such receptors to promote elimination of HLA-I+ tumor cells. As proof of concept, we show here that a chimeric antigen receptor (CAR) can be engineered to overcome inhibition by receptors for HLA-I and to promote lysis of HLA-I+ tumor cells by CAR-NK cells. The design of this NK-tailored CAR (NK-CAR) relied on the potent NK cell activation induced by the synergistic combination of NK receptors CD28H (CD28 homolog, TMIGD2) and 2B4 (CD244, SLAMF4). An NK-CAR consisting of the single-chain fragment variable (scFv) of a CD19 antibody, the CD28H transmembrane domain, and the fusion of CD28H, 2B4, and TCR signaling domains was compared to a third-generation T-cell CAR with a CD28-41BB-TCR signaling domain. The NK-CAR delivered stronger activation signals to NK cells and induced more robust tumor cell lysis. Furthermore, such CAR-NK cells could overcome inhibition by HLA-E or HLA-C expressed on tumor cells. Therefore, engineering of CAR-NK cells that could override inhibition by HLA-I in patients undergoing cancer immunotherapy is feasible. This approach offers an attractive alternative to more complex strategies, such as genetic editing of inhibitory receptors in CAR-NK cells or treatment of patients with a combination of CAR-NK cells and checkpoint blockade with antibodies to inhibitory receptors. A significant benefit of inhibition-resistant NK-CARs is that NK cell inhibition would be overcome only during contact with targeted tumor cells and that HLA-I on healthy cells would continue to maintain NK cell responsiveness through licensing.